PENGUASAAN KONSEP FISIKA PESERTA DIDIK DALAM PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI KOMUNIKASI DAN EKSPERIMEN LABORATORIUM - Drikben Eka Putra Nggadas (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2019)
This study aims to examine differences between the mastery of physics concepts taught learners through information communication technology based learning and learners are taught through the study of laboratory experiments based learning. The study population was a class X SMA Negeri 4 Kupang, which is in the second semester of academic year 2012/2013. This type of research is quasiexperimental with pretest-posttest design with nonequivalent groups of two experimental classes treated with information communications technology based learning and laboratory experiments based learning and a control class that was treated with conventional learning. Data were collected through a written test and analyzed using independent samples t test using SPSS 16.0 for Windows. The results showed that there is a difference between the mean mastery of physics concepts taught learners through information communication technology based learning and learners are taught through the study of laboratory-based experiments. The mean mastery of physics concepts taught learners through information communication technology based learning higher than students taught through the study of laboratory experiments based learning.